Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Adaptive Peacebuilding Programming Through Effective Feedback Loops: Promising Practices - Barnard-Webster, Kiely; Jean, Isabella (CDA, 2018)
This case study report was developed by CDA’s part of Peacebuilding Evaluation Consortium collaborative research on the use of feedback loops in support of adaptive programming. Feedback loops are just one element of adaptive programming and are defined and used in different ways by organizations working on social change, peace and development issues. This document includes key findings from our desk review of reports and grey literature, key informant interviews, observations documented during CDA’s advisory and learning engagements with peacebuilding partners as well as the case study on SFCG’s feedback processes in Burundi. The findings are most relevant to program and M&E staff but have implications for senior management and policymakers in light of growing interest in strengthening adaptive management.

Snapshot of Adaptive Management in Peacebuilding Programs - Queen, Emily Forsyth; Baumgardner-Zuzik, Jessica; Hume, Elizabeth; Greenberg, Melanie (Alliance for Peacebuilding, 2018)
The Alliance for Peacebuilding developed the report Snapshot of Adaptive Management in Peacebuilding Programs with support from Humanity United. This report examines how existing organizational programs are designing and learning from adaptive management in a conflict effected and fragile states. It further provides practical recommendations for applying adaptive management to peacebuilding programs based on synthesis … Continue reading "Snapshot of Adaptive Management in Peacebuilding Programs"
Keywords: KEY

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability – The country context–Burundi from 1999 to 2014 – Ingos in peacebuilding–globally unaccountable, locally adaptive – International organizations in peacebuilding–globally accountable, locally constrained – Bilateral development donors–accountable for global targets, not local change
OCLC: 1048387754

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.